2021
DOI: 10.1016/j.ijmmb.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid antigen detection kit for the diagnosis of SARS-CoV-2 - are we missing asymptomatic patients?

Abstract: Purpose To determine the utility, diagnostic accuracy, sensitivity, specificity, and negative predictive value of the laboratory based Covid-19 antigen detection test (Coris Bio- Concept, Gembloux, Belgium) for the diagnosis of SARS-CoV-2 in a tertiary care hospital among symptomatic and asymptomatic patients. Methods The nasopharyngeal swab samples were collected from the symptomatic patients and their contacts. The diagnostic accuracy of this antigen kit was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Lower sensitivity was also observed in samples that showed high Ct values in RT-PCR [17][18][19]24,[26][27][28][30][31][32][33][34]36,38,39,42,43,47,53], indicating a lower viral load. In SARS-CoV-2 infection, the viral load peaks in the first week after the onset of symptoms in the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Lower sensitivity was also observed in samples that showed high Ct values in RT-PCR [17][18][19]24,[26][27][28][30][31][32][33][34]36,38,39,42,43,47,53], indicating a lower viral load. In SARS-CoV-2 infection, the viral load peaks in the first week after the onset of symptoms in the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 95%
“…Suboptimal sensitivity was also observed in samples with low viral loads (high Ct value in RT-PCR) [17][18][19]24,[26][27][28][30][31][32][33][34]36,38,39,42] and in pediatric samples, when compared with samples from adult patients [22,24,25,28]. Only two studies showed values of specificity lower than 98% (64.2% and 83.3%) [36,42].…”
Section: Direct Detection Testsmentioning
confidence: 95%
See 2 more Smart Citations
“…The Cochrane Report confirmed the value of all the above factors when using RATs for widespread diagnostic purposes [23]. Another study spoke of the benefits of RATs involving 'triage and emergencies' needing priority diagnoses [24]. RATs have long been used for diagnosing other illnesses, such as pharyngitis caused by Streptococcus bacteria [25] and Bancroftian filariasis [26].…”
Section: Rats In Clinical Settings In Indiamentioning
confidence: 99%